Teacher’s perspectives on designing and evaluating the i-Kalam application to learn the Arabic speaking skill - Alif Fahmi Abdullah,; Taufik Ismail,; Muhammad Sabri Sahrir,; Muhammad Izzat Mohd Abd Shukur, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Our current era has witnessed rapid development in the field of modern technology until it has come to dominate all matters of daily life and in various aspects of life, including in the field of teaching and learning. Smartphones are part of modern technology that can be used in the field of teaching and learning. This study aimed to reveal teachers’ perspectives in designing and evaluating the “i-Kalam” application to develop Arabic speaking skill. This study relied on a qualitative research approach using a semi-structured interview as a tool for collecting data. The sample of the study consisted of three teachers who teach the Contemporary Arabic Language subject to form one students according to the Integrated Religious Curriculum at Sekolah Menengah Agama Al-Madrasah Ad-Diniah Al-Alawiyah in Arau, Perlis. The researchers analyzed the data using Atlas.ti version 9.0. The results of the study indicated that teachers have a positive perception of using the application to learn the Arabic speaking skill. This study also discovered the appropriate study contents, educational activities and evaluation methods for inclusion in the i-Kalam application. This study also identified the required facilities and appropriate mobile technology devices and platforms to conduct mobile learning. This study also discovered the problems and challenges faced while conducting the mobile learning process, as well as suggestions for improving the problems and challenges faced while conducting the mobile learning process.